Determination of Nutritional Habits and Physical Activity Levels of Healthcare Professionals - Tan, Cetin; Tan, Suriye; Erdogan, Ramazan (Mattioli 1885, 2020)
In this study, it was aimed to examine the nutritional habits and physical activity levels of healthcare professionals. 131 (67 women, 64 men) volunteer healthcare professionals working in health institutions in Elazig participated in the study. Personal Information Form was used to determine the demographic information of the participants, Nutritional Habits and Nutrition Information Levels developed by Yticel (2015) to determine the nutritional habits and knowledge levels, and the International Physical Activity Survey short form was determined to determine the physical activity levels. SPSS package program was used to analyze the data. In the study, p<0.05 was accepted as significant. According to the results of the research, 55% of healthcare professionals did not have any nutrition education, and 68.7% were not doing any sports. It was found that none of the participants had any chronic diseases. In our study, 53.4% of the participants were having 3 main meals a day, 63.4% were not having breakfast regularly, 53.4% were skipping meals during the day, and the most skipped meal was breakfast. Missing meal was mostly because not having time, and 41.2% of them were having one snack, 29% were consuming carbonated drinks between meals, 32.8% were drinking 2 liters of water daily. It was determined that 35.1% of participants were preferring meals less salty, 35.1% of them were eating fast. Emotional status was affecting eating less as 34.4% when they were sad, and 38.2% when they were happy. It was determined that the healthcare professionals participating in the study had low physical activity levels. Even if there were no statistically significant data between nutritional status, knowledge and demographic variables, there was a statistically significant difference between physical activity levels and their profession levels. As a result; it was stated that healthcare professionals do not have a regular healthy lifestyle and their physical activity levels were low. In this context, we believe that there is a need for educations that encourage regular physical activity and a healthy lifestyle for healthcare professionals.
Keywords: Nutrition; Healthcare Professionals; Nutritional Habit; Physical Activity